The Issue of Commitment in Literature: A Study of Olafioye’s Selected Poems - Jide, Ogidan; Nelson, Adevemo (International Journal For Research In Educational Studies, 2016)
The African public has always demanded that the work of their writers be committed to some socio-political cause bothering on the citizens. In this paper, attempt is made at trying to explain what is meant by commitment in literature. This will enables African writers us to discover the term commitment, or how an artist gets committed. In Nigeria today, a category of poetry which is combative in its questioning of the socio-political and economic structures is becoming increasingly popular. When compared with independence poets, the poets in this category are more aggressive in their criticism of their society. There is a high degree of commitment to the search for a well ordered society where there is a reasonable level of social justice and progress in society. Tayo Olafioye belongs to this new generation of poets. Some of his poems in parliament of idiots will be used to establish the thematic concern of this work.